The loop-forming method as a useful technique to rotate the endoscopic insertion tube shaft - Suga, Tomoaki; Okamura, Takuma; Arakura, Norikazu; Tanaka, Eiji (Endoscopy International Open, 2016)
Background and study aims: Gastroenterological endoscopists are instructed to bring the target to the 6-o'clock position when they take a biopsy specimen, use a snare, or cut a target organ. This action is performed primarily by rotating the shaft of the endoscopic insertion tube, which can be difficult in some situations when existing endoscopic methods are used. We previously described a method for optimal rotation of the endoscopic insertion tube shaft, called the loop-forming method (LFM). The present study aimed to validate this procedure and confirm the usefulness of the LFM for leftward rotation of the shaft. Participants and methods: The LFM was specifically taught to 28 gastroenterological endoscopists, and the angle of rotation was measured before and after they received instruction in this method. Results: The LFM significantly increased the average angle of leftward rotation from 266° to 327°. Moreover, whereas the instrument channel inlet tended to move away from the right hand of an operator using a conventional endoscopy method, it remained closely accessible to the right hand of an examiner using the LFM.Conclusions: The LFM has the potential to make endoscopic procedures easier and safer.